The Effect of Additives of Corn Flour and Corn Forage Fraction (Zea mays L.) in Making Silage on the Content NDF ADF - Oktria Dinindra; Sr Mulyani; F Fridarti (Fakultas Pertanian Universitas Tamansiswa Padang, 2023)
This study aims to determine the effect of additives of corn flour and corn forage fraction (Zea mays L.) in making silage on the content NDF ADF. This research was carried out on Street Kaliberantas No. 19 Alai Parak Kopi Padang and analyze in the Ruminant Nutrition Laboratory Faculty of Animal Science Andalas University Padang. This research was conducted by experiment method using a Completely Randomized Design (CRD) with a factorial pattern with 2 factors namely factor A is Forage corn which consists of 2 fractions namely : a1= Upper Fraction, a2= Lower Fraction. Factor B is the content of corn flour additives which consists of 3 levels namely b1= 4%, b2= 8%, b3=12% with 4 replications. The measure Variable is Neutral Detergent Fiber (NDF) dan Acid Detergent Fiber (ADF). The result showed that the additives up to 12% to Silage using forage corn had a significant effect (P<0,05) on the NDF content, while the ADF content had no significant effect (P>0,05) on silage.